Profile of Parenting Style in University Students with Tendency of Hedonism Lifestyle - Maura Tuzzahrah; Erikavitri Yulianti; Lilik Djuari (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2019)
Introduction: This research is to determine the profile of parenting style with tendency of hedonism lifestyle in university students of Medicine Program Faculty Of Medicine Airlangga University Batch 2015.Methods: This study is a observational analytic research with cross-sectional time and used questionnare as research instrument given to 200 respondentsResults: : 16 university students raised with authoritarian parenting style (8.30%), 169 students raised with authoritative parenting style (87.56%), and 8 students raised with permissive parenting style (4.14%). Students with tendency of hedonism lifestyle in category low is 45 students (23.32%), in category intermediate is 146 students (75.64%), and in category high is 2 students (1.04%). Tendency of hedonism lifestyle is  low in 2 students raised with authoritarian parenting style (1.04%), 42 students raised  with authoritative parenting style (21.76%), and 1 students raised with permissive parenting style (0.52%). Tendency of hedonism lifestyle in category intermediate has 12 students raised with authoritarian parenting style (6.22%), 127 students raised with authoritative parenting style (65.80%), and 7 students raised with permissive parenting style (3.62%). In category high tendency of hedonism lifestyle is 2 students raised with authoritarian parenting style (1.04%). Using Kruskal-Willis test, it was found that p = 0.123 .Conclusion: Most parenting style used in the students is authoritative. Category of tendency of hedonism lifestyle in most students is category intermediate. Tendency of hedonism lifestyle in category low has most students raised with authoritative parenting style. Tendency of hedonism lifestyle in category intermediate has most students raised with authoritative parenting style. Tendency of hedonism lifestyle category high has most students raised with authoritarian parenting style. And it was found that there is no significant difference in proportion in parenting style with the tendency of hedonism lifestyle with value of  p = 0.123  with α = 0.05 (p>α)